2014
DOI: 10.1038/cdd.2014.86
|View full text |Cite
|
Sign up to set email alerts
|

CD300b regulates the phagocytosis of apoptotic cells via phosphatidylserine recognition

Abstract: The CD300 receptor family members are a group of molecules that modulate a variety of immune cell processes. We show that mouse CD300b (CLM7/LMIR5), expressed on myeloid cells, recognizes outer membrane-exposed phosphatidylserine (PS) and does not, as previously reported, directly recognize TIM1 or TIM4. CD300b accumulates in phagocytic cups along with F-actin at apoptotic cell contacts, thereby facilitating their engulfment. The CD300b-mediated activation signal is conveyed through CD300b association with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
85
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 50 publications
0
85
1
1
Order By: Relevance
“…Overexpression of human CD300 family members has shown that CD300f tends to form homodimers, but CD300f can also form heterodimers with other CD300 family members. 42 Human CD300a 27 and mouse CD300b 30 share PS as a ligand and are known to inhibit or potentiate efferocytosis, respectively. Whether or not CD300 heterodimer formation is unique to humans and occurs in the absence of overexpression remains to be determined.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overexpression of human CD300 family members has shown that CD300f tends to form homodimers, but CD300f can also form heterodimers with other CD300 family members. 42 Human CD300a 27 and mouse CD300b 30 share PS as a ligand and are known to inhibit or potentiate efferocytosis, respectively. Whether or not CD300 heterodimer formation is unique to humans and occurs in the absence of overexpression remains to be determined.…”
Section: Resultsmentioning
confidence: 99%
“…The phagocytosis of liposome-coated beads has been described previously. 30 Briefly, BMDC stained with PKH26 (Sigma-Aldrich) were incubated with PS-containing-liposome-coated beads for 30 min. Cells were collected and suspended in ice-cold homogenization buffer (0.25 M sucrose, 10 mM HEPES (pH7.4), protease inhibitor cocktail (Roche) in PBS), and then lysed by passage through a bended 27.5 gauge needle 20 times.…”
Section: Phagocytosis Of Ac or Ps-containing-liposome-coated Beadsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the recognition of ceramide by mouse CD300f or of ceramide and sphingomyelin by human CD300f induces the suppression of various inflammatory responses (15,(21)(22)(23)(24). CD300a, CD300b, CD300c, or CD300f binds to phosphatidylserine, thereby positively or negatively regulating apoptotic cell-mediated immune responses (16,17,19,20). The binding of T-cell immunoglobulin and mucin domain 1 (TIM-1) to CD300b accelerates renal ischemia/reperfusion injury (14).…”
Section: Introductionmentioning
confidence: 99%
“…CD300 members are mainly expressed in myeloid cells and contain a highly homologous single immunoglobulin-like domain in their extracellular regions; CD300a (LMIR1 or CLM-8) and CD300f (LMIR3 or CLM-1) are inhibitory receptors that harbor immunoreceptor tyrosine-based inhibitory motif (ITIM) in their cytoplasmic regions, while other CD300 members are thought to be activating receptors that are coupled with adaptor proteins [e.g., FcRγ and DNAX-activating protein 12 (DAP12)] bearing immunoreceptor tyrosine-based activating motif (ITAM) (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Multiple studies showed that lipids or lipid-binding proteins act as ligands for several members of mouse and human CD300 family (14)(15)(16)(17)(18)(19)(20). For example, the recognition of ceramide by mouse CD300f or of ceramide and sphingomyelin by human CD300f induces the suppression of various inflammatory responses (15,(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%